Evaluación del efecto de tres niveles de cáñamo ( Cannabis sativa) como promotor de crecimiento en pollos broiler (Gallus gallus) en la parroquia San Simón, Guaranda - Fierro Montero, Adrián David (2025)
The study evaluated the effect of three levels of hemp (Cannabis sativa) as a growth promoter in broiler chickens (Gallus gallus) in the San Simón Parish, Guaranda. The specific objectives were to establish the best level of cannabis in broiler chicken rearing, determine which of the three levels of cannabis has the best results in feed conversion, and develop an economic analysis of the benefit/cost ratio. The research analyzed the effect of different cannabidiol (CBD) treatments on the growth of broiler chickens to determine the impact on their development. Measurements were taken of the initial and weekly weight of the chickens fed with water and balanced feed, as well as with various concentrations of CBD. In the first week, treatment T4 showed the highest average weight (154.10 g), although there were no significant differences between treatments. As the weeks progressed, treatment T4 continued to stand out, reaching a weight of 1248.17 g in the fourth week, being the only one that showed significant differences compared to other treatments. In the fifth week, treatment T3 (15% CBD) presented the highest weight gain (2013.37 g), followed by T4 (1985.60 g), which allowed establishing that the level of cannabis influences growth. Feed conversion was better in T3 (1.38 g/g), indicating the most efficient level in terms of feeding. The profitability analysis indicated that T4 was the most profitable, with a coefficient of 1.10, fulfilling the objective of evaluating the benefit/cost ratio. Mortality was 9 animals during the study, which demonstrated that the treatments were safe. It was concluded that the addition of CBD positively influences the growth of chickens, and its use in the fattening diet is recommended. Furthermore, it is suggested to investigate its application in other poultry species to evaluate its effectiveness in growth and intestinal health.